An improved LEA block encryption algorithm to prevent side-channel attack in the IoT system - Choi, Jaehak; Kim, Youngseop (2016 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference (APSIPA), 2016)
Devices of IoT (Internet of Things) are limited in resources such as CPU, memory etc. The LEA (Lightweight Encryption Algorithm) was standardized as the encryption algorithm suitable for IoT devices in Korea in 2013. However, LEA is vulnerable to the side-channel analysis attack using consumed electric power. To supplement this vulnerability, masking technique is mainly used. However, in case of masking process, the implementation time is increased, losing the characteristics of speedup and lightening. This paper proposes a new and faster LEA algorithm as a countermeasure to the side-channel attack. The proposed algorithm is about 17 times faster than existing algorithms with the masking process to prevent differential side-channel attack.